Incidence and warning signs for complications of human brucellosis: a multi-center observational study from China - Qing-Nan Shi; Hui-Jie Qin; Qiao-Shan Lu; Shu Li; Zhong-Fa Tao; Meng-Guang Fan; Mu-Heta Aishan; Zeng-Qiang Kou; Qiu-Lan Chen; Wen-Wu Yin; Yan-Ping Zhang (Infectious Diseases of Poverty, 2024)
Abstract Background Brucellosis is a severe zoonotic disease that is often overlooked, particularly in impoverished countries. Timely identification of focal complications in brucellosis is crucial for improving treatment outcomes. However, there is currently a lack of established indicators or biomarkers for diagnosing these complications. Therefore, this study aimed to investigate potential warning signs of focal complications in human brucellosis, with the goal of providing practical parameters for clinicians to aid in the diagnosis and management of patients. Methods A multi-center cross-sectional study was conducted in China from December 2019 to August 2021. The study aimed to investigate the clinical characteristics and complications of patients with brucellosis using a questionnaire survey and medical record system. The presence of warning signs for complications was assessed using univariate and multivariate logistic regression models. Receiver operating characteristic (ROC) curves and the area under the curve (AUC) were used for variable screening and model evaluation. Results A total of 880 participants diagnosed with human brucellosis were enrolled. The median age of the patients was 50 years [interquartile range (IQR): 41.5–58.0], and 54.8% had complications. The most common organ system affected by complications was the osteoarticular system (43.1%), with peripheral arthritis (30.0%), spondylitis (16.6%), paravertebral abscess (5.0%), and sacroiliitis (2.7%) being the most prevalent. Complications in other organ systems included the genitourinary system (4.7%), respiratory system (4.7%), and hematologic system (4.6%). Several factors were found to be associated with focal brucellosis. These factors included a long delay in diagnosis [odds ratio (OR) = 3.963, 95% confidence interval (CI) 1.906–8.238 for > 90 days], the presence of underlying disease (OR = 1.675, 95% CI 1.176–2.384), arthralgia (OR = 3.197, 95% CI 1.986–5.148), eye bulging pain (OR = 3.482, 95% CI 1.349–8.988), C-reactive protein (CRP) > 10 mg/L (OR = 1.910, 95% CI 1.310–2.784) and erythrocyte sedimentation rate (ESR) elevation (OR = 1.663, 95% CI 1.145–2.415). The optimal cutoff value in ROC analysis was > 5.4 mg/L for CRP (sensitivity 73.4% and specificity 51.9%) and > 25 mm/h for ESR (sensitivity 47.9% and specificity 71.1%). Conclusions More than 50% of patients with brucellosis experienced complications. Factors such as diagnostic delay, underlying disease, arthralgia, eye pain, and elevated levels of CRP and ESR were identified as significant markers for the development of complications. Therefore, patients presenting with these conditions should be closely monitored for potential complications, regardless of their culture results and standard tube agglutination test titers.